Removal and immobilization of arsenic from wastewater via arsenonatroalunite formation. Issue 19 (24th August 2022) - Luo, Zhongqiu; Mu, Weihong; Zhou, Xintao; Chen, Zhuo
ABSTRACT: Removal and immobilization of highly toxic arsenic form industrial wastewater using simple and effective methods is of important practical significance. Although the formation of natroalunite phase NaAl3 (SO4 )2 (OH)6 has been demonstrated to be an effective method for arsenic immobilization in model system with chemical reagent grade arsenates as arsenic source, the further study is needed to investigate its immobilization for real industrial wastewater. This work reported the synthesis of natroalunite phase NaAl3 (SO4 )2 (OH)6 using arsenic-containing industrial wastewater from benzyl acid production. The synthesis temperature and time were optimized to obtain the pure natroalunite phase composites with high crystallinity. When n (Al/As)aq was greater than 3.0, the arsenic could almost precipitate exclusively as natroalunite phase after 60 min hydrothermal reaction at 200°C, with a maximum arsenic immobilization amount of 7.0 mol%. A maximum leaching concentration of 0.50 mg/L was observed at pH = 3.0 during the short-term (24 h) leaching test, which was lower than the US EPA TCLP test limit of 1 mg/L. The long-term leaching test up to 90 days revealed that the arsenonatroalunite could be a safe immobilization material for arsenic in pH 5.0–8.0 environments. GRAPHICAL ABSTRACT: UF0001